Generative Artificial Intelligence (GAI) as an adaptation machine: tensions between authorship and recombination in audiovisual media - Souza, Natacha de; Torres, David Ruiz (Farol, 2026)
This article investigates Generative Artificial Intelligence (GAI) as an audiovisual adaptation system, analyzing its effects on authorship and creation based on text prompts. By transforming a single input into images, sound, and editing, GAI automates adaptive processes and reconfigures the narratives and aesthetics of pre-existing works. Drawing on a dialogue between adaptation studies and critical AI studies, the article examines GAI as a type of “adaptation machine,” problematizing the boundaries between original creation and recombination, with an emphasis on the prompt as a semiotic operator and an act of mediation.